Os relatórios das Delegacias Regionais de Ensino do Estado de São Paulo como fonte de pesquisa para a História da Educação - décadas de 1930 e 1940 - Celeste Filho, Macioniro [UNESP] (My University, 2012)
From 1933 to 1944, the 21 Regional Offices of Education of the State of São Paulo worked out reports of inventory of the schools of São Paulo inspected in that period of time. At least 68 of those reports have been preserved in the Public Archive of the State of São Paulo. The current paper presents part of that patrimony as an important source of research for the history of education. By dividing that documentation between visual and written sources, the text will focus on the visual sources, and will discuss the methodological difficulties of using this kind of source. Following, will be illustrated part of the visual information that those documents offer to the researchers. The article concludes with a brief sampling of textual information that the reports provide to the historians.

De 1933 a 1944, as 21 Delegacias Regionais de Ensino do Estado de São Paulo elaboraram relatórios inventariando as escolas paulistas inspecionadas no período. Ao menos 68 desses relatórios foram preservados no Arquivo Público do Estado de São Paulo. O atual artigo apresenta parte desse acervo como importante fonte de pesquisa para a história da educação. Ao dividir essa documentação entre fontes visuais e fontes escritas, o texto privilegiará as fontes visuais. Serão debatidas as dificuldades metodológicas do uso deste tipo de fonte. Na sequência, será exemplificada parte das informações visuais que esses documentos possibilitam aos pesquisadores. O artigo se encerra com uma breve amostragem das informações textuais que os relatórios fornecem aos historiadores.
The reports of the Regional Offices of Education of the State of São Paulo as a source of research for history of education – decades of 1930 and 1940
Keywords: History of education; Documentary sources; São Paulo education; School groups; Images and historical research; História da educação; Fontes documentais; Ensino paulista; Grupos escolares; Imagens e pesquisa histórica